Hashimoto’s Thyroiditis: An Overview of Current Evidence from the Literature - Dworak, Michał; Kowalska, Marta; Mazur, Anna; Brodziak, Julia; Werenkowicz, Wiktor; Ciszewska, Wiktoria; Kosztyła-Czech, Zofia; Wiśniewski, Tomasz; Matyja, Mateusz (Journal of Education, Health and Sport, 2026)
Introduction and purpose Hashimoto’s thyroiditis is the most prevalent autoimmune disorder of the thyroid and a primary cause of hypothyroidism. It occurs predominantly in women and often manifests with vague, nonspecific complaints, which may also be present in euthyroid patients, leading to delayed recognition. Although levothyroxine remains the cornerstone of therapy, a subset of patients continues to report ongoing symptoms. This review outlines current evidence regarding the epidemiology, pathophysiology, clinical presentation, diagnostic approach, and both established and emerging therapeutic options for this condition. A brief description of the state of knowledge Hashimoto’s thyroiditis is a frequent autoimmune disease and the leading cause of hypothyroidism in many populations. Its pathogenesis involves an interplay of genetic predisposition, environmental factors, and dysregulation of the immune response. Clinical manifestations are heterogeneous and may include fatigue, depressive symptoms, and cognitive difficulties, even in the presence of normal thyroid hormone levels. Diagnosis is based on clinical evaluation supported by laboratory assessment of thyroid hormones and antibodies, as well as ultrasound imaging. While levothyroxine effectively normalizes biochemical parameters in most cases, persistent symptoms are commonly reported. This has led to growing interest in adjunctive interventions such as selenium, vitamin D, and inositol supplementation, acupuncture, and lifestyle modification. Increasing attention is also being paid to the influence of the gut–thyroid axis, including the potential role of probiotics in immune modulation. An individualized and more comprehensive treatment strategy may benefit patients with an incomplete response to standard therapy. Conclusions Hashimoto’s thyroiditis is a multifactorial autoimmune condition that often necessitates an individualized therapeutic approach. Persistent symptoms despite appropriate treatment are common. Integrating conventional management with supportive measures may enhance clinical outcomes and improve patients’ quality of life.